Medication-related osteonecrosis of the jaws associated with intravitreal administration of ranibizumab. Issue 12 (December 2020) - Oz, I.; Kaplan, I.; Kleinman, S.; Arbel, S.; Shuster, A.
Abstract: Medication-related osteonecrosis of the jaws (MRONJ) is a well-known complication that, in the majority of cases, is related to antiresorptive agents. Numerous articles have described cases of MRONJ in bisphosphonate-naïve patients treated with anti-angiogenic agents administered via various routes. A single case of MRONJ after intravitreal injection of bevacizumab has been reported. We report a case of MRONJ after intravitreal injection of a different anti-angiogenic agent – ranibizumab – for the treatment of neovascular age-related macular degeneration, in a bisphosphonate-naïve patient. Although it may be a rare complication, patients treated with multiple doses of anti-angiogenic agents should be monitored for the possible early diagnosis of MRONJ.